Fiscal stabilisation and EMU - Robert Woods (Center for Economic Studies and ifo Institute (CESifo), 2004)
This paper builds on the discussion paper published by HM Treasury in 2003 alongside the UK Government's assessment of the case for EMU entry. The paper considers the potential for fiscal policy to play a greater role in stabilisation policy if the UK were inside EMU. The paper considers: the scope for strengthening the automatic stabilisers and the possible tradeoffs; how institutional changes could increase the effectiveness of discretionary fiscal policy; which fiscal instruments might be the most effective; and to what extent stabilisation might be promoted in other ways, such as through enhanced risk sharing by financial markets.
Keywords: E63; E62; 330; Finanzpolitik; Konjunkturpolitik; Europäische Wirtschafts- und Währungsunion; Eingebauter Stabilisator; Diskretionäre Politik; Grossbritannien